Perception of students about primary science classes of GPS of Bangladesh - A K M Obaydullah, Dr. (SPC Journal of Education, 2020)
According to the record most of the PEC examination, the quality of science was the below among other subjects. Even internal examination results also showed the same picture. Students cannot achieve satisfactory level of the competency of science. This study analysis revealed varies dimensions of the studentsâ€™ perceptions that relate to different aspects of the teacherâ€™s pedagogy and the learning environment created by the teachers, like: student center learning, class Environment, use of teaching aids and modern equipments, positive attitude of teacher, feedback, etc. The study was qualitative and quantitative in nature. It was decided to select samples from Dhaka and Gazipur district under the Dhaka division of Bangladesh. Total 40 government primary schools (GPS) selected from the selective area. For this study, data collected from 80 student focus group discussion (FGD) by questionnaire method from 40 different GPS. Also 80 science classes were observed for realizing actual teaching-learning situations and document study. Most of the school hasnâ€™t use of multimedia, modern class room, library and science equipment. Utmost of the teachers never used teaching aids. Students always needed help from others. Maximum students don't interaction with the teacher in the classrooms. At the annual and PEC examinations of 2018 the students who failed in different subjects, they also failed in science. The study recommended that student teacher ratio should be reduced by appointing new teacher, quality based supervision should be improved. Science subject training are much needed for all school. Science class time should be increase.Â Â Â